Comparing the Developmental Complexity of Different Game Engines by Creating the Same Game Using Two Different Engines - Normalisa, Normalisa; Atmadiputra, Pradana; Prawiko, Jibran Wafi (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Game development is often considered to be a vague topic. With many beginner programmers interested in independent game development as an occupation, one must find out where should they start. Determining a first game engine could be a difficult choice for someone, and many beginner programmers hoped that their skills and early experiences could be utilized in the game development environment. Many comparisons do not detail what makes one game engine more difficult to learn than the other, and would only present vague terms such as because one engine can create a more complex game, yet it does not state how that would affect a game engine’s learning curve. Research must be conducted to clear out this vagueness. Inside a game is basically a series of objects interacting with one another. Therefore, it should not be a problem when a developer switches between game engines, and yet these developers could have a faster development time when using a different engine. The result of this research is to determine how that difference is possible by comparing the developmental process of two different game engines (gamemaker and Godot) and determine which one is objectively better than the other in specific terms.